Estudo da aderência em perfis tubulares de aço preenchidos com concreto geopolimérico - Laura Beatriz Medina Duarte (2017)
Portland Cement production is commonly associated with high CO2 emissions and it is also considered an energy intensive process. As a result, engineering and science have been looking for solutions to reduce emission and energy consumption. In the searching of sustainable solutions the use of alkali activated cements, also called geopolimeryc cements is highlighted. Nowadays steel-concrete structures are being implemented in civil construction as an alternative for the use of structural elements with better performance and lower cost. This paper presents experimental studies about the adherence and behavior of geopolymeric concrete-filled steel tubes. Four models were designed and four prototypes per model were tested. The first and second model have rectangular cross sections with and without longitudinal cuts respectively. The third model presents square cross sections without a longitudinal cut and the final model has circular cross sections without longitudinal cut. In the experiment, two prototypes of each model were filled with geopolymeric concrete-steel tubes, while the other two with concrete-steel tubes, for a total of sixteen tests. A compressed axial load was applied to the concrete core of each prototype, the steel tube was used as support of each test to allow relative sliding between the two materials. The results show a difference in the performance of geopolymeric concrete, and concrete-filled steel tubes. Another finding was of this study was the increase of the shear transfer between steel and geopolymeric concrete